Liquidity risk and performance of banking industry: case study of top-3 local bank of Malaysia / Mahathir Zainal Abidin - Abidin, Mahathir Zainal (Faculty of Business Management, 2017)
In Malaysia, the awareness of liquidity risk of the bank is not really give more responsiveness. By doing this study can help some of people to know about liquidity risk. Another problem is to define the breakeven point symptom of the liquidity risk. This is because the liquidity risk is hard to be predict for the future. This research of the objective to examine between deposit, cash, liquidity gap and non-performing loan with bank total assets. To meet this objective, the data of the analysis have been taken from the annual reports of Top-3 of local bank in Malaysia. This study focus on conventional bank because Islamic bank have different risk management structure. The data have been collected for a set of three banks for the period of 2001–2015. The nature of the data is panel data. The data will be run on Regression Analysis mean while the relationship between dependent and independent variables will be tested by Correlation Analysis. Bank total assets will be dependent variable for this research meanwhile independent variables are deposit, cash, liquidity gap and non-performing loan.